Peningkatan Kompetensi Guru PAUD di Kecamatan Mojoagung Melalui Pelatihan Berbasis Experiential Learning - Imrotul Ummah; Rachma Hasibuan (Lembaga Pengembangan Kinerja Dosen, 2024)
This research is motivated by the problem of competence of Early Childhood Teachers in Mojoagung District which is not yet in accordance with the competency demands mandated by Minister of Education and Culture Regulation No. 137 of 2014 concerning PAUD Standards. They need training to improve the competency of preschool teachers so they are able to provide learning for early childhood in accordance with the latest PAUD National Curriculum currently in effect. This research aims to find a training model that can improve the competence of PAUD educators. To achieve the aim of this research is to develop a competency training model with an experiential learning approach so that after being trained, the competency of PAUD educators can increase in accordance with the mandate of Minister of Education and Culture Regulation No. 137 of 2014 concerning PAUD Standards. This research uses a qualitative approach. Data collection techniques use questionnaires, interviews, observation and documentation studies. The data analysis technique uses a qualitative approach. The research results show that: The results of data analysis show that there are four themes that are the main focus in Experiential Learning-based training. These aspects of involvement are: 1) The teacher's understanding of the competence of Early Childhood Teachers after participating in Experiential Learning-based training, 2) Plans for implementing Experiential Learning into learning, 3) Special aspects in Experiential Learning training that help understand the needs and characteristics of Aud 4) Readiness to create a learning environment based on Experiential Learning in Early Childhood Classes. The implications of the research results are discussed further in the article.